A marine turbocharger retrofitting platform - Ntonas, Konstantinos; Aretakis, Nikolaos; Roumeliotis, Ioannis; Mathioudakis, Konstantinos (ASME, 2021)
A turbocharger retrofitting platform utilizing 1D models for calculating turbomachinery components maps and a fully coupled process for integration with the turbomachinery components and the diesel engine, is presented. The platform has been developed with two modes of operation, allowing the retrofitting process to become fully automatic. In the first mode, available turbo-components are examined, in order to select the one that best matches the entire engine system, aiming to retain or improve the diesel engine efficiency. In the second mode, an optimization procedure is employed, in order to redesign the compressor to match the entire system in an optimum way. Dimensionless parameters are used as optimization variables, for a given compressor mass flow and power. A retrofitting case study is presented, where three retrofitting options are analyzed (compressor retrofit, turbocharger retrofit and compressor redesign). In the first and second option, turbocharger retrofitting is carried out, using available turbo-components. It is shown that initial performance cannot be reconstituted using off-the-self solutions. In the third option, compressor designing is performed, using the optimization mode, in order to provide an improved retrofitting solution, aiming to at least reconstituting the original diesel engine performance. Finally, a CFD analysis is carried out, in order to validate the compressor optimization tool capability to capture the performance trends, based on geometry variation
Keywords: Geometry; Flow (Dynamics); Engines; Computational fluid dynamics; Turbomachinery; Compressors; Turbochargers